Eleven-year descriptive analysis of closed court verdicts on medical errors in Spain and Massachusetts. Issue 8 (30th August 2016) - Giraldo, Priscila; Sato, Luke; Martínez-Sánchez, Jose M; Comas, Mercè; Dwyer, Kathy; Sala, Maria; Castells, Xavier
Abstract : Objectives: To evaluate and compare the characteristics of court verdicts on medical errors allegedly harming patients in Spain and Massachusetts from 2002 to 2012. Design, setting and participants: We reviewed 1041 closed court verdicts obtained from data on litigation in the Thomson Reuters Aranzadi Westlaw databases in Spain (Europe), and 370 closed court verdicts obtained from the Controlled Risk and Risk Management Foundation of Harvard Medical Institutions (CRICO/RMF) in Massachusetts (USA). We included closed court verdicts on medical errors. The definition of medical errors was based on that of the Institute of Medicine (USA). We excluded any agreements between parties before a judgement. Results: Medical errors were involved in 25.9% of court verdicts in Spain and in 74% of those in Massachusetts. The most frequent cause of medical errors was a diagnosis-related problem (25.1%; 95% CI 20.7% to 31.1% in Spain; 35%; 95% CI 29.4% to 40.7% in Massachusetts). The proportion of medical errors classified as high severity was 34% higher in Spain than in Massachusetts (p=0.001). The most frequent factors contributing to medical errors in Spain were surgical and medical treatment (p=0.001). In Spain, 98.5% of medical errors resulted in compensation awards compared with only 6.9% in Massachusetts. Conclusions: This study reveals wide differences in litigation rates and the award of indemnity payments in Spain and Massachusetts; however, common features of both locations are the high rates of diagnosis-related problems and the long time interval until resolution.